BOBOT POTONG, KARKAS, GIBLET DAN LEMAK ABDOMINAL AYAM BROILER YANG DIBERI GULA MERAH DAN KUNYIT DALAM AIR MINUM SEBAGAI FEED ADDITIVE - Wiesje M. Horhoruw; Rajab Rajab (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2019)
The aim of the research was to know effect of palm sugar and curcumma as feed addtive on slaughtering weight, carcass, giblet, and abdominal fat weight of broiler. Total of 90 tail of broiler (COBB strain) with DOC weight rate was 37 g used as experimentas materials rearing in 38 days. This research used analysis of varianve method of complete random design with 3 treatments and 5 replication was observed, there was P0 = without feed additive, P1 = using feed additive (palm sugar 2 % and 10 g of curcumma), dan P2 = using feed additive (palm sugar 2 % and 20 g of curcumma). The results showed that there was no significance effect of palm sugar and curcumma as feed addtive on slaughtering weight, carcass, giblet, and abdominal fat weight of broiler.